2020
DOI: 10.1146/annurev-matsci-082319-111001
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Thermoelectrics

Abstract: Constructing hybrid composites with organic and inorganic materials at different length scales provides unconventional opportunities in the field of thermoelectric materials, which are classified as hybrid crystal, superlattice, and nanocomposite. A variety of new techniques have been proposed to fabricate hybrid thermoelectric materials with homogeneous microstructures and intimate interfaces, which are critical for good thermoelectric performance. The combination of organic and inorganic materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 130 publications
0
40
0
Order By: Relevance
“…Although TE technology is direct, simple, and environmentally friendly, its sluggish progress over the past few decades is partly due to the lack of efficient TE semiconducting materials and the low conversion efficiencies (η < 5%) [4][5][6][7][11][12][13][14][15][20][21][22][23]. Nevertheless, for TE technology to be practically viable and competitive with PV technology for harvesting solar energy, the TE semiconductors should exhibit ZT values ≥ 1 or PF ≥ 4 mW/m.K 2 [3,4,7,[11][12][13][14][15]. Today, TE technology development becomes a top priority to harvest waste heat associated with fuel engines, small domestic devices, solar thermal radiation, and other heat sources.…”
Section: Pf = () S 2 (3) Zt = (/) S 2 T (4)mentioning
confidence: 99%
See 3 more Smart Citations
“…Although TE technology is direct, simple, and environmentally friendly, its sluggish progress over the past few decades is partly due to the lack of efficient TE semiconducting materials and the low conversion efficiencies (η < 5%) [4][5][6][7][11][12][13][14][15][20][21][22][23]. Nevertheless, for TE technology to be practically viable and competitive with PV technology for harvesting solar energy, the TE semiconductors should exhibit ZT values ≥ 1 or PF ≥ 4 mW/m.K 2 [3,4,7,[11][12][13][14][15]. Today, TE technology development becomes a top priority to harvest waste heat associated with fuel engines, small domestic devices, solar thermal radiation, and other heat sources.…”
Section: Pf = () S 2 (3) Zt = (/) S 2 T (4)mentioning
confidence: 99%
“…Current research in this field is unfolding on utilizing solar thermal energy to build solar-based TE systems [24,25]. However, the success of this technology relies on obtaining p-type and n-type TE semiconductors that are characterized by narrow bandgap exhibiting sufficiently high σ and S values while displaying low κ [3][4][5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23]. Recent reports showed that the microstructure of TE materials as displayed by the grain size and morphology (texture, crystallinity, dimensionality) significantly affect the transport of charge carriers and phonons scattering.…”
Section: Pf = () S 2 (3) Zt = (/) S 2 T (4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Energy crisis and environmental problems are serious issues for human society because they could cause a huge loss to economy and materials. The conversion of waste heat to electric power by means of thermoelectric (TE) devices has become more and more crucial in the new energy era. , TE materials with no mechanical moving parts, no obnoxious emission, lightweight, pollution-free, and compact structures are promising new energy materials, which directly realize the conversion between thermal energy and electric energy , through Seebeck and Peltier effects . The properties of TE materials are characterized by the dimensionless value, ZT = S 2 σ/κ, where S is the Seebeck coefficient, σ is the electrical conductivity, and κ is the thermal conductivity. ,,, , Obviously, in order to achieve a high ZT value, high Seebeck coefficient, high electrical conductivity, and low thermal conductivity are required, but these parameters are interdependent and are determined by the electronic structure (band gap, band shape, and band degeneracy near the Fermi level) and the scattering of charge carriers (electrons or holes) and phonons . The balance between the electrical conductivity and the Seebeck coefficient is crucial to attain the maximum power factor (PF = S 2 σ). Lots of attempts have been made to improve the power factor of TE materials, including quantum-well structures, crystals with complex structures, multilayer films, enhancing the molecular chain order, controlling the doping level, and organic–inorganic nanocomposites .…”
Section: Introductionmentioning
confidence: 99%